Analysis of Comparative Advantages and Export Potential of Indonesian Green Tea in the International Market - Rif'an Hariri (Universitas Darussalam Gontor, 2025)
Green tea is an export commodity produced by Indonesia. This commodity is produced from tea plantations in Indonesia. Currently, the value and volume of green tea exports are still lower than those of black tea. Therefore, it is necessary to study the comparative advantage and potentialexportfor green tea in the international market. The novelty in this research is combining the comparative advantages and export potential of green tea which has not been researched previously. This study aims to analyze the comparative advantageand potential exportof Indonesian green tea in the international market.The data used is Indonesian green tea export from 2006 to 2023. The data sources are UN Comtrade and the Central Statistics Agency.This study used the revealed comparative advantage (RCA) method, the trade specialization index, export product dynamic (EPD) method and X model. The results obtained indicate that the comparative advantage of green tea in the international market is relatively weak, as evidencedby the RCA value of less than 1. The trade specialization index is positive. A positive trade index indicates that Indonesia is classified as a green tea exporter. The weakening of Indonesia's comparative advantage in green tea has not impacted its position in the international market. The position of green tea in international trade based on export product dynamics is still in the rising star position, which means that Indonesian green tea is still in a profitable position.Based on the X model, Indonesian green tea still has the potential to be developed in the international market.